1985
DOI: 10.1121/1.392453
|View full text |Cite
|
Sign up to set email alerts
|

Constancy of (acoustic) relative timing measures in phrase-level utterances

Abstract: The hypothesis that acoustic measures of relative speech timing remain constant across large changes in speaking rate was tested for fluent utterances produced by normal and neurogenically disordered speakers. For all speakers, relative timing tended to be statistically invariable across conversational and fast speaking rates. This finding was considered especially interesting in the case of speakers with dysarthria and apraxia of speech, because absolute measures of speech timing associated with these disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This linear relationship remains invariant across changes in speaking rate and stress. (Similar constancies in relative timing of acoustic events, across changes in rate, have been reported by Weismer & Fennell 1985. ) Kelso & Tuller (1985) have further analysed their movement data in terms of phase and have shown that the consonant gesture begins at a fixed phase angle in the vowel cycle.…”
Section: Specification Of Gestures and Inter-gestural Relationssupporting
confidence: 80%
“…This linear relationship remains invariant across changes in speaking rate and stress. (Similar constancies in relative timing of acoustic events, across changes in rate, have been reported by Weismer & Fennell 1985. ) Kelso & Tuller (1985) have further analysed their movement data in terms of phase and have shown that the consonant gesture begins at a fixed phase angle in the vowel cycle.…”
Section: Specification Of Gestures and Inter-gestural Relationssupporting
confidence: 80%
“…Most studies exploring the relationship between aging and speech were exclusively limited to participants under the age of 80 years [2][3][4], and those including older populations were limited to normal elderly, with relatively high levels of cognitive functioning and without a diagnosis of dementia [5].…”
Section: Introductionmentioning
confidence: 99%
“…The observed consistency in the relative timing (or phase angle stability) between the upper lip and jaw existed despite changes in rate and stress. Stability across suprasegmentaI changes has also been observed in the electromyographic activity of perioral muscles (Tuller et al, 1982(Tuller et al, , 1983, oral-laryngeal coordination during voiceless consonant production (Lofqv[st and Yoshioka, 1984), ranges of tongue blade movement during CV transitions (Beckman et al, 1984;Fujimura, 1984Fujimura, , 1986, and even in the acoustic signal during sentence production (Weismer and Fennell, 1985). Similar phase invariance has also been reported in coordinated movements of the hand (e.g., Scholz and Kelso, 1989; Tuller and Kelso, 1989).…”
Section: Introductionmentioning
confidence: 81%